Aide à l'apprentissage du discours oral dans un contexte de communication asynchrone - John Fynn (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
We have developed our VoiceForum software solution to solve a basic problem regarding how to help learners in L2 spoken interaction activities. In a task-based approach, which is facilitated by the present trend towards groupware solutions, we discuss the problem of giving learners immediate feedback on their oral work. At the centre of this problem, trainers are faced with the dilemma of knowing whether to focus on meaning or on form. We have observed that focusing on form greatly inhibits interaction.To get round this problem, VoiceForum works asynchronously. It enables learners to talk together by posting spoken messages on a forum. Another function of the software is to enable the tutor to create tailor-made help items in the form of positive or negative feedback linked to the individual messages. These help items are contextualised and therefore of greater relevance to the learners. The help remains accessible over time within the forum and a search tool facilitates its consultation. Our hypothesis is that creating help items in this way builds up a new dynamic resource which will be more efficient than the current practice of giving participants a feedback list at the end of each discussion activity.